Detection of formal thought disorders in child and adolescent psychosis using machine learning and neuropsychometric data - Zakowicz, Przemysław T.; Brzezicki, Maksymilian A.; Levidiotis, Charalampos; Kim, Sojeong; Wejkuć, Oskar; Wiśniewska, Zuzanna; Biernaczyk, Dominika; Remberk, Barbara
Formal Thought Disorder (FTD) is a significant clinical feature of early-onset psychosis, often associated with poorer outcomes. Current diagnostic methods rely on clinical assessment, which can be subjective and time-consuming. This study aimed to investigate the potential of neuropsychological tests and machine learning to differentiate individuals with and without FTD.
Keywords: zaburzenia myślenia; psychoza; diagnoza medyczna; metody diagnozy; testy neuropsychologiczne